2019
DOI: 10.3390/molecules24081474
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ethyl Carbamate during the Production Process of Cantonese Soy Sauce

Abstract: The aim of this work was to clarify the formation of ethyl carbamate (EC) and its influence factors throughout the production process of Cantonese soy sauce. The results showed that EC was not detected in the koji-making and early moromi fermentation stages, but started to be generated when pH of the moromi decreased to about 4.9—at the same time, the levels of ethanol, urea and citrulline increased significantly. Most EC was formed during raw soy sauce hot extraction (40.6%) and sterilization (42.9%) stages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Although Saccharomyces cerevisiae can produce citrulline via arginine metabolism, the generation of citrulline is majorly attributed to the metabolism of arginine by malolactic bacteria via the ADI pathway (Fang et al, 2018). In previous work, citrulline content in moromi was found to continuously increase throughout the fermentation period, and it was significantly accumulated when fermented from 20 to 90 days in Cantonese soy sauce (Zhou et al, 2019). In this study, we isolated 34 strains from moromi and determined their arginine utilization ability.…”
Section: Key Strains For Citrulline Accumulationmentioning
confidence: 90%
See 1 more Smart Citation
“…Although Saccharomyces cerevisiae can produce citrulline via arginine metabolism, the generation of citrulline is majorly attributed to the metabolism of arginine by malolactic bacteria via the ADI pathway (Fang et al, 2018). In previous work, citrulline content in moromi was found to continuously increase throughout the fermentation period, and it was significantly accumulated when fermented from 20 to 90 days in Cantonese soy sauce (Zhou et al, 2019). In this study, we isolated 34 strains from moromi and determined their arginine utilization ability.…”
Section: Key Strains For Citrulline Accumulationmentioning
confidence: 90%
“…Citrulline and ethanol are considered to be the major EC precursors in soy sauce ( Matsudo et al, 1993 ; Zhou K. et al, 2017 ; Zhou et al, 2019 ). However, reducing ethanol content may damage the quality of soy sauce, since a certain amount of ethanol has a major contribution to the flavor and spice taste of soy sauce.…”
Section: Introductionmentioning
confidence: 99%
“…The ethyl carbamate concentration in each sample was measured using a gas chromatography–mass spectrometry (GC–MS) method [ 19 ]. For each analysis, 4 g of sample was homogenized with 4 mL of distilled water and then sonicated for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al (2016) reported that the citrulline content of soy sauce declined from 26.8 to 5.1 mM, and the EC decreased from 97 to 17 µg/kg when B. amyloliquefaciens JY06 was supplemented during the fermentation. However, slight changes in the soy sauce flavor were noticed (Zhou et al, 2019). To determine and screen precursors and their impact on EC formation during soy sauce production, high-performance liquid chromatography with fluorescence detection has been implemented for the quick and efficient quantification of EC, which could help create hazard analysis and critical control points for soy sauce production (Zhou et al, 2017).…”
Section: By-product Eliminationmentioning
confidence: 99%
“…Another concern is the by-products generated during manufacturing, including ethyl carbamate (EC), a Group 2A carcinogen formed by arginine-consuming bacteria in the moromi mash. Efforts have been made to reduce EC accumulation using salt-tolerant strains, but slight changes in the soy sauce flavor have been reported (Zhang et al, 2016;Zhou et al, 2019). Another by-product is soy sauce residue (SSR), with about 4,500,000 tonnes of SSR is generated annually, and it is usually discarded without suitable application although it contains many nutrients such as proteins and oil.…”
mentioning
confidence: 99%